Characterization of physical properties Kuantan bauxite - Nurmazuria, Mazelan (2019)
In Kuantan there was an origin mineral and geochemistry of Bauxite had been formed, however less knowledge and experience in handling the Bauxite had cause air and water pollution around the Bauxite area. The Bauxite area has been banned once but the government of Kuantan had decided to construct a new development area on the Bauxite soil. This study, as it can be specify the bauxite is a rock that contain a lot of composition and it takes place in different texture in form. An investigation of engineering characterization and physical properties of the bauxite had been carry out at different site in Kuantan for future research about Kuantan bauxite. Laboratory test had been done at three different sites where the sites is at Semambu, Bukit Goh and Indera Mahkota. This investigation is to identify the physical properties of the bauxite at Kuantan sites by do the lab test of moisture content, particle size distribution, atterberg limit and specific gravity. The result had been compared and refers from the other researchers and journal to prove whether this research had achieve the objective or not. Referring to the other researchers and journals, this research objective had been achieved and prove that the result of bauxite sample that had been taken for laboratory testing was in the range of bauxite soil.